Benefits of an intergenerational program in the early years - Emily Kirsh; Erica Frydenberg; Jan Deans (Journal of Early Childhood Education Research, 2021)
Intergenerational programs unite the young and old in shared activities to foster positive relationships across generations, reducing loneliness caused by living in residential care and improving children’s attitudes toward the elderly. This study evaluated an intergenerational program in 2019 between an Early Learning Centre (ELC) associated with a metropolitan university in Melbourne, Australia, and a residential aged care facility. The program provided opportunities for the children to engage and participate in their society, increase the social connections within communities, and develop their social emotional skills. This study explored 4- and 5-year-olds’ attitudes towards older people, empathy, prosocial behaviour, and coping strategies through a multimethod approach. 32 children from the intergenerational program and 25 children from a regular ELC group were interviewed about their experience with older people while their teachers completed empathy and coping questionnaires. Results showed children in both groups had positive attitudes towards older people. Children enjoyed making friends, singing songs together, building social connections, and learning about the older adults’ life stories; they were encouraged and supported to see themselves as citizens of a community. The paper explores the value of qualitative interviews with participating teachers, children, and parents for a more informative evaluation.